Internet use and adolescent development in rural China: A scoping review protocol of research landscape and gaps. - Linxiao Zhang (PLoS ONE)
Introduction In the digital era, the Internet has become a necessity in adolescents' daily lives. Many studies globally are exploring the influences of Internet use on adolescent development, but they focus on the negative impacts of simplistic "screen time" on adolescents' physical and mental health, rather than both positive and negative influences of multifaceted Internet use on multidimensional adolescent development. Specifically in rural China, adolescents live in disadvantageous and marginalizing contexts, and Internet use is widespread among this population. However, knowledge on Internet use and adolescent development in rural China is fragmented. It is still unclear in what ways Internet use would bring benefits or risks for Chinese rural adolescents' healthy growth. Therefore, the objective of this scoping review is to identify the current research landscape, gaps, and future directions in rural China contexts. It aims to provide a comprehensive overview of elements, findings, and limitations in existing empirical studies on the influences of Internet use on adolescent development in rural China. Materials and methods The standard for conducting this scoping review is the five-stage model proposed by Arksey and O'Malley, and the reporting standard is the Preferred Reporting Items for Systematic Reviews and Meta-Analyses: Extension for Scoping Reviews (PRISMA-ScR). The overall research question is: What are the influences of Internet use on adolescent development in rural China? In consultation with librarians, to locate articles, subject headings (controlled vocabularies) and textwords (keywords) in article titles, abstracts, and author-assigned keywords will be searched in APA PsycInfo (psychology), China National Knowledge Infrastructure (interdisciplinary), Communication Abstracts (media and communication), Education Source (education), MEDLINE (public health), Social Services Abstracts (social work), Social Work Abstracts (social work), and Sociological Abstracts (sociology). The review process via Covidence will consist of two sequential steps based on inclusion/exclusion criteria: the title and abstract review and the full-text review. Then study characteristics and research findings will be charted, and the results will be analyzed and synthesized quantitatively and qualitatively via visualizations and narratives, guided by the typological frameworks of Internet use and adolescent development. Discussion The scoping review will be a pioneering review to inform the current research landscape and gaps in the Internet use influences on adolescent development in rural China. It will advance the research agenda on this issue conceptually, theoretically, and empirically. In addition, it can provide contextual implications for designing prevention and intervention programs.